Immune regulation of autoimmune diabetes: the role of regulatory t(t-reg) cells & ppar gamma - Nor, Norazmi Mohd (Pusat Pengajian Kesihatan, 2015)
RM The immunodownregulatory function of nTreg cells is critical in mediating peripheral self-tolerance. The transcription factor, Foxp3, has been established to be crucial for the function of nTreg cells. Another anti-inflammatory molecule, peroxisome proliferatoractivated receptory (PPARyfflhas also been previously shown to have immunoregulatory properties. The current study was conducted to determine the modulatory mechanism of nTreg cells following treatment with the PPARy ligand, ciglitazone, in isolated nTreg cells of BALB/c, as well as in the Type 1 diabetes or autoimmune mouse model, Non Obese Diabetic (NOD) as well as in the control, Non Obese Resistant (NOR) mice. Optimization of culture duration, concentration of IL-2, and functional analyses were performed on cultured nTreg cells from BALB/c mice in vitro. The expression levels of PPARy isoforms as well as PPARy binding activity to its response elements, PPRE, was examined in treated and untreated nTreg cells to determine whether the oberved responses were PPARy-dependant or -independant. Results showed that there were no binding of PPARy to PPRE in the treated nTreg cells of BALB/c, NOD or NOR mice. PPARy ligand treatment also did not cause phosphorylation of the transcription factors ZAP-70 and STAT-5 in these mice. nTreg cells was found to constitutively expressed low levels of PPARyl and PPARy2. Upon treatment with ciglitazone PPARyl but not PPARy2 expression was induced via PPARy-dependant pathway (P < 0.01). PPARy ligand downregulated the expression of Foxp3 in nTreg cells of BALB/c, NOD and NOR mice via a PPARy-independant pathway compared to untreated group (P < 0.01). Various pro-inflammatory pathway-related target genes were downregulated in NOD nTreg cells following treatment with ciglitazone compared to those of NOR mice. The downregulation of Foxp3 expression by PPARy ligand in nTreg cells may downregulate the immuno-regulatory function of these cells in mice, especially autoimmune diabetic mice.